Health Care System for Immigrants (Accessibility, Quality, Cost) - Michailidou, Evangelia Michail (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2020)
The aim of this study is to identify and describe within the existing literature the characteristics (Immigrant, accessibility, quality, cost.) of primary health care models of service delivery for Indigenous immigrant people. Our focus was on knowledge synthesis of maternity care among immigrants to Greece provided a coherent evidence base for (a) eliciting a better understanding of the factor that generate disparities in accessibility, acceptability, and outcomes during maternity care and (b) improving culturally-based competency in maternity care. Our synthesis also identified pertinent issues in multiple sectors that should be addressed to configure maternity services and programs appropriately. Effectiveness, safety, and patient experience are key components of healthcare quality, an important element of health systems performance.